PERAN TEKNOLOGI BLOCKCHAIN DALAM MENINGKATKAN TRANSPARANSI LAPORAN KEUANGAN : A SYSTEMATIC LITERATUR REVIEW - Aldina Syifa Nur Irmadhani; Totok Dewayanto (Diponegoro Journal of Accounting, 2025)
This research aims to examine the role of blockchain technology in improving the transparency of financial statements in the field of accounting and finance. The Systematic Literature Review (SLR) method was used to analyze 34 Scopus-indexed scientific articles published between 2017-2025. The results show that blockchain has great potential in creating secure, transparent, and irreversible transactions, as well as promoting real-time financial reporting and faster decision-making. The implementation of smart contracts and Triple-Entry Accounting (TEA) also improves record-keeping efficiency and audit automation. However, the implementation of these technologies still faces challenges such as regulatory constraints, security risks, low financial and technological literacy, and technical costs and complexities. This research emphasizes the importance of financial professional adaptation and the need for blockchain standards and regulations to ensure transparency and compliance globally.